The Vitality of Reality Distortion in Tim Burton’s The Nightmare Before Christmas - Kurniawati, Wiwin Anggraeni; Siadari, Yoshua Veron Handika Putra; Pasopati, Rommel Utungga; Andharu, Devito; Fadillah, Muhammad Reza Ishadi (SALIENCE: English Language, Literature, and Education Journal, 2025)
This writing investigates about the distorted reality portrayed in the Tim Burton’s movie called The Nightmare Before Christmas. The film follows the misadventures of Jack Skellington, Halloweentown's beloved pumpkin king, who has become bored with the same annual routine of frightening people in the "real world.” When Jack accidentally stumbles on Christmas town, all bright colors and warm spirits, he plots to bring Christmas under his control by kidnapping Santa Claus and taking over the role. The theory behind the world portrayed in The Night Before Christmas is about distorted reality that is a term used to describe a phenomenon where perceptions of reality are altered or distorted in some way. Using a qualitative method and explorative approach, this essay analyses the distorted reality showed in the Halloween Town. The architecture is angular with distorted shapes and lines reflecting the way Burton felt as an outcast and the way society views the strange and different. Moreover, the characters in the film live in a world of perpetual horror and ‘nightmarishness’, but that is their comfort and normality. In conclusion, The Nightmare Before Christmas indicates that reality distortion may not always be eerie, but may mean to reflect ‘otherness’ and unique perspectives of another world.